2012
DOI: 10.1016/j.neurobiolaging.2012.03.013
|View full text |Cite
|
Sign up to set email alerts
|

ADAM10 expression and promoter haplotype in Alzheimer's disease

Abstract: Alzheimer’s disease is confirmed at autopsy according to the accumulation of brain neuritic plaques and neurofibrillary tangles in the brain. Neuritic plaques contain Aβ and lower levels of Aβ correspond to an increase in ADAM10 α-secretase activity. ADAM10 α-secretase activity produces a soluble APP alpha (sAPPα) product and negates the pathological production of Aβ. In this investigation it was hypothesized that genetic variation with the ADAM10 promoter is associated with ADAM10 expression levels as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(52 citation statements)
references
References 32 publications
2
50
0
Order By: Relevance
“…In the cases with AD, extensity scores of immunohistochemical staining for β-APP (51-75%vs51-75%), ADAM9 (50-75%vs26-50%), ADAM10 (76-100% vs 0-25%), and ADAM17 (76-100%vs 0%) were detected as indicated in parentheses [unpublished observations). Bekris et al [65] reported elevated CSF sAPPα levels in cognitively normal subjects compared with patients with AD and higher hippocampus ADAM10 protein levels in subjects with a low neuritic plaque score compared with those with a high neuritic plaque score. ADAM10 mRNA expression is higher in AD patients compared with control subjects in cerebellum, but not in hippocampus [65].…”
Section: The Proven Functions Of Adam Proteases In Admentioning
confidence: 99%
See 2 more Smart Citations
“…In the cases with AD, extensity scores of immunohistochemical staining for β-APP (51-75%vs51-75%), ADAM9 (50-75%vs26-50%), ADAM10 (76-100% vs 0-25%), and ADAM17 (76-100%vs 0%) were detected as indicated in parentheses [unpublished observations). Bekris et al [65] reported elevated CSF sAPPα levels in cognitively normal subjects compared with patients with AD and higher hippocampus ADAM10 protein levels in subjects with a low neuritic plaque score compared with those with a high neuritic plaque score. ADAM10 mRNA expression is higher in AD patients compared with control subjects in cerebellum, but not in hippocampus [65].…”
Section: The Proven Functions Of Adam Proteases In Admentioning
confidence: 99%
“…Cleavage of APP by α-secretase releases a large, soluble N-terminal ectodomain, soluble α-secretase-released Nterminal APP domain (sAPPα), into the extracellular space [62]. Several studies have reported that α secretases exerted proteolytic effects on APP preventing production, and accumulation of Aβ proteins in AD [22,[62][63][64][65]. The important roles of ADAM9, -10, and -17 in these processes such as APP amyloid cascade, functioning of pathogenetic processes, and subtypes of amyloid proteins are already known [22,63,64].…”
Section: The Proven Functions Of Adam Proteases In Admentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, in the trophic, anti-amyloidogenic anti-AD pathway, APP is cleaved by an α-secretase (putatively ADAM10) to generate the two fragments sAPPα and αCTF. These latter fragments [30] support synaptic maintenance and can inhibit the β pathway as cleavage at the α site precludes β cleavage and because sAPPα itself is a BACE inhibitor [31,32].…”
Section: App Processingmentioning
confidence: 99%
“…Alternatively, in the trophic, anti-amyloidogenic anti-AD pathway, APP is cleaved by an α-secretase (putatively ADAM10) to generate the two fragments sAPPα and αCTF. These latter fragments [30] support synaptic maintenance and can inhibit the β pathway as cleavage at the α site precludes β cleavage and because sAPPα itself is a BACE inhibitor [31,32].The interaction of APP cleavage products with each other and non-APP-derived proteins is complex and the mechanisms by which these APP fragments exert their many effects is not fully elucidated [34]. It is known, however, that αCTF can inhibit γ-secretase activity [33] as it contains an intact γ-cleavage site.…”
mentioning
confidence: 97%